Legal expediency aspects of the position of academics in the composition of the notary supervisory board in Indonesia - Rozella Yuniditia; Mohammad Ryan Bakry; Chandra Yusuf (SEAN Institute, 2024)
This study analyzes the role of academics in the Supervision of Notary Supervision Panels in Indonesia and the concept of legal expediency of the role of academics in the Composition of Notary Supervisory Panels. The formulation of the problem proposed is what is the role of academics in the Supervision of Notary Supervisory Panels in Indonesia and how is the legal expediency of the role of academics in the Composition of Notary Supervisory Panels. This research uses a normative juridical approach, data collection is carried out by literature study and data analysis is carried out qualitatively. The results of this study show that: first, the role of academics in the Supervision of Notary Supervision Panels in Indonesia is to provide a balance of views based on academic theories on the types of violations reported and the types of sanctions to be imposed in accordance with the severity of errors or violations of the code of ethics committed by reported notaries. Academic views are submitted to the plenary session of the Supervisory Panel and formulated jointly regarding the types of violations committed and legal sanctions imposed on the reported notary. Furthermore, the court will decide the case and the verdict will be handed down as the decision of the Supervisory Panel. Second, the legal expediency of the role of academics in the composition of the Notary Supervisory Panel is of significant benefit in carrying out supervision of notaries, especially providing a balance of views academically in handling cases against notaries who commit violations. In addition, it provides benefits in the organizational development of the Notary Supervisory Council, especially in transforming knowledge in the latest notarial fields for the organization, organizational development through education and training as well as the implementation of research and evaluation in order to improve the quality of the Notary Supervisory Council's performance.